Conference Record of the Thirty-Eighth Asilomar Conference on Signals, Systems and Computers, 2004.
DOI: 10.1109/acssc.2004.1399120
|View full text |Cite
|
Sign up to set email alerts
|

Will ET write or radiate: inscribed matter vs. electromagnetic channels

Abstract: Abstract-We consider the energy requirements of information carriage using physical transport of inscribed matter and compare it to that using electromagnetic radiation when delivery delay beyond light transit time can be tolerated. Somewhat counter-intuitively, physical transport of inscribed matter is often more energy efficient than electromagnetic broadcast by many orders of magnitude over a wide range of scenarios -from chipto-chip computer communications to interstellar signaling. In fact, the efficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Previous work on mobile wireless communication found that network capacity could be increased if delay-tolerant traffic was queued until the receiver and sender were close to one another -perhaps close enough to exchange physical storage media [18]- [31]. This recognition prompted a careful consideration of the energetics involved in delivery of physical messages, and a series of papers [32]- [34] revealed the surprising results that inscribed matter can be many orders of magnitude more efficient than radiative methods even with moderate delay constraints and over a variety of size scales. In fact, [34] showed that over interstellar distances (10k light years), inscribed matter could be on the order of 10 15 times more energy-efficient than radiated messages, suggesting that evidence of extraterrestrial civilizations would more likely come from artifacts than from radio messages if energy requirements are a proxy for engineering difficulty [35].…”
Section: B Communication Using Physical Objects: An Engineering Persp...mentioning
confidence: 99%
“…Previous work on mobile wireless communication found that network capacity could be increased if delay-tolerant traffic was queued until the receiver and sender were close to one another -perhaps close enough to exchange physical storage media [18]- [31]. This recognition prompted a careful consideration of the energetics involved in delivery of physical messages, and a series of papers [32]- [34] revealed the surprising results that inscribed matter can be many orders of magnitude more efficient than radiative methods even with moderate delay constraints and over a variety of size scales. In fact, [34] showed that over interstellar distances (10k light years), inscribed matter could be on the order of 10 15 times more energy-efficient than radiated messages, suggesting that evidence of extraterrestrial civilizations would more likely come from artifacts than from radio messages if energy requirements are a proxy for engineering difficulty [35].…”
Section: B Communication Using Physical Objects: An Engineering Persp...mentioning
confidence: 99%